Pengembangan Pantai Glagah Sebagai Objek Wisata Daerah Kulon Progo Yogyakarta - Emmita Devi Hari Putri - AKPAR BSI Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2012)
ABSTRACT - Glagah beach is one beach which is located in the Kulon Progo regency which is about 40 km from the city of Yogyakarta. The author takes as the title of thesis Glagah beach because the beach is a beach Glagah seeded in Kulon Progo Regency. Glagah Beach has a lot of objects and the means to do the refreshing. Another attraction Glagah beach excellent place to fly kites, as well as for lovers of motor racing to racing in a motocross event. Neither party kite and motocross. One of the developments that will be done by the government is developing a culinary tourism as a tourist attraction stu sala. In writing this essay the author uses the theory to know strength SWOT analysis strenght, weakness , opportunity, and threats as the retrieval results of the analysis. The results of analysis in the form of development strategy including tourist attractions pengadan strategy, the strategy increased cooperation with investors, the new image creation strategies, strategies to improve facilities and infrastructure.Keywords: Development, Culinary Tourism, Community Income